The counter‐trafficking apparatus in action: who benefits from it? - Clemente, M. (2022)
Based on long-term ethnographic research, including documentary research, quali- tative interviews and observations made at a Portuguese shelter for “sex trafficked women,” this paper explores the counter-trafficking apparatus questioning who ben- efits from it. The discussion explores the contrasts between an institutional commit- ment to constructing this apparatus and the actuality of procedural efforts purporting to support “trafficking victims.” I argue that the higher goal of building a counter- trafficking apparatus — in itself a political objective — limits the rights of “vic- tims,” making processes that claim to be part of their protection de facto neo-liberal anti-political exercises in reenforcing bureaucratic state power.